Sinyal Indeks dan Imbalan Masa Depan Dari Imbalan dan Resiko Masa Lalu pada Investasi Saham Syariah di Indonesia - Muhammad Anhar (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2021)
Abstract- This research aims to proove the existing signal of Indonesia sharia stock’s risk and return to their future index and return. The hypothesis state that the past stock’s risk and return respectly give a signal on their future index and return.The research is designed as a quantitative, ex post facto, associative, and positivistic research by analyzing the correlation of the past stock’s risk and return to their future index and return.The stock risk (total risk, systematic risk and unsystematic risk) and return are set as independent variables, while stock’s future index and return as dependent variables.The existing signals were studied simultaneously in one model, Partial Least Square (PLS). Descriptive analysis, Correlations analysis, and hypotheses testing were done in this study.The conclusions were : First, the past stock’s return do not give any signal to their future index and return. Second, the total risk, systematic risk and unsystematic risk respectly give a signal to their future return, but do not to their future index. Third, the total risk and unsystematic risk respectly give a negative signal to their future return, while the systematic risk do a positive signal.